The Influence of OWL-Plantation System Application towards Employees Performance in Indonesia: A study case at PT Sebakis Inti Lestari (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
The study seeks to determine and analyze the effect of the OWL - Plantation System application towards employee’s performance at PT. Sebakis Inti Lestari. It was conducted at PT. Sebakis Inti Lestari and the sample consisted of 40 office workers. Purposive sampling is a non-probability sampling technique of superior quality in which the researcher creates a limit based on the characteristics of the subjects to be sampled. The investigation employs SPSS version 25 for data analysis. According to the findings of this study, the OWL – plantation system significantly impacts employee performance.